Application of laser deprocessing technique in PFA on chemical over-etched on bond-pad issue. (September 2016) - Yap, H.H.; Tan, P.K.; Zhu, L.; Feng, H.; Zhao, Y.Z.; He, R.; Tan, H.; Liu, B.; Huang, Y.M.; Wang, D.D.; Lam, J.; Mai, Z.H.
Abstract: With technology scaling of semiconductor devices and further growth of the integrated circuit (IC) 1 design and function complexity, the package size has shrank down proportionally too. Hence, flip-chip solder bump mounting is the current semiconductor devices trend to replace the wire bonding technology. When come to PFA 2 on the flip-chip devices with solder bump, wet etch for solder bump removal is an essential method. Upon using wet etch methodology; it is very dependent on etching timing and the chemical aggressiveness to get a good removal result for the solder bump. If there is an excessive period in etching or chemical reacts too aggressively, chemical over-etched on bond pad will occur. It is very unfavorable for FA 3 engineer to perform subsequent reverse engineering on the bond pad over-etched device. In this paper, the application of laser deprocessing technique is proposed to solve the bond pad over-etched issue. This proposed technique is a quick and reversal way in deprocessing technique for defect identification in PFA. Highlights: Poor chemical removal handling that resulting bond-pad with craters and harsh to handle for subsequent top down deprocessing Methodology to solve the chemical over-etched on bond-pad issue The technique is a quick and reversal way in deprocessing technique for defect identification in PFA.